PEMETAAN KESUBURAN PERAIRAN MENGGUNAKAN CITRA SATELIT AQUA MODIS DI PANTAI BARAT – SELATAN NANGGROE ACEH DARUSSALAM - Heru Arafat; Vincentius P Siregar (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2021)
This research was conducted to observe variations in the distribution of chlorophyll-a and sea surface temperature (SST) along the west to south coast of Nanggroe Aceh Darussalam (NAD) Province. These results will be used to identify potential fishing area s. Variations in the distribution of chlorophyll-a and SST using Aqua MODIS satellite data from January 2006 to December 2010 and catch statistics data for the province of NAD. the concentration of chlorophyll-a for 5 years along the west-south coast of NAD varied but rather low, the total concentration of chlorophyll-a was around 0.15-0.45 mg/m³. The concentration of chlorophyll-a is higher in the west monsoon compared to other seasons of the year, because high rainfall in that season causes a higher supply of nutrients. SST was warmer and higher in 2010, the SST value was around 28.7-31.9 °C. SST increases in the west season to the transition season, then decreases in the east season. In general, the SST along the west-south coast of NAD is above 27 °C which means these waters are warm. The relationship between chlorophyll-a concentration and Catch per Unit Effort (CPUE) is not very influential, because CPUE used for this calculation are all types of herbivorous fish and carnivorous fish. However, based on the optimal temperature, the pelagic fishing area ranges from 28-30 °C, so it can be said that the west and northeast seasons are very good for fishing.